Trade in Services : global regulation and the impact on key service sectors - Raworth, Philip (Oceana Pub. Dobbs FerryUS, 2005)
Focuses on the liberalization of trade in services at the international level. Looks at the various barriers and measures that prohibit, restrict or make more costly the supply of services by a provider from one country to a recipient from another country. Explains how the major international or regional agreements attempt to remove them. Discusses the liberalization of financial, telecommunications and transport services as well as government procurement.